Tracking the Performance of Listed Shares: A Comparison Between JSE Single- and Dual-listed Shares - Muller, Mariska; Ferreira-Schenk, Suné; Rensburg, John George Jansen van; Mokatsanyane, Daniel; Sgammini, Ruschelle (International Journal of Economics and Financial Issues, 2022)
The measurement of a stocks return over a time period is analysed for several reasons. The most obvious and most important one is to inform investors’ expectations regarding future earnings potential. Therefore, the study made a comparison using the financial performance of single-listed shares versus dual-listed shares that trade primarily on the South African stock market (JSE). The time-period for the comparison of financial performance of single- and dual-listed shares was from 2005 to 2020 to confirm or refute the general perception surrounding superior returns of dual-listed companies as opposed to single-listed companies. Utilising financial ratios can be imperative when making informed judgments about investment portfolios. Seven of the most important financial ratios were used to measure the performance of company shares within nine specified industry sectors in South Africa. These included the earnings per share ratio (EPS), price-earnings ratio (P/E), market to book value ratio (M/B), current ratio (CR), debt to equity ratio (DER), and the return on equity ratio (ROE). The nine identified industries included the transport, consumer staples, printing, pharmaceutical, mining and manufacturing, technology, luxury goods and services, financial services, and real estate industries. The results indicate that the dual-listed companies do indeed outperform single-listed companies on the JSE for the majority of the financial ratios over the specified period. This study contributes to portfolio management by informing equity allocation in the short-term and long-term.